Pade approximation for extended boundary condition method in electromagnetic scattering analysis - Abu-Zald, NA; Tosun, H (Wiley, 2002)
The Pade approximation technique in conjunction with the extended boundary condition method (EBC) is implemented to solve the scattering problem over a finite frequency interval. The algorithm is based on expanding the system equations in their power series, and then finding a recurrence relation for the series coefficients. Fairly good results are obtained. (C) 2002 John Wiley & Sons, Inc.
Keywords: Pade approximation; extended boundary condition method